A case analysis of the viability of the current regulation and enforcement mechanisms of corporate governance in Zambia - Mwanawasa, Chipokota (Department of Commercial Law, 2016)
The narrative has changed. It is no longer 'Africa is rising' but 'Africa has risen'. Africa's economic potential is being sung from all corners of the world. One would think that the continent would undergo another 'scramble for Africa' following on from this economic boom. However, it is also clear that all this growth and foreign investment into African development cannot be embraced in the absence of proper commercial institutional structures and policy guidelines in the areas of corporate governance. While these structures may already exist to some degree, the areas of greatest concern are those of enforcement and regulation. This dissertation therefore examines the case for strengthening the regulation and enforcement mechanisms of corporate governance in Africa using Zambia as a case study. After an analysis of the law and the institutional framework surrounding corporate governance in Zambia, it becomes evident that the current self-regulatory system is weak and inadequate in terms of ensuring compliance: this shortcoming ultimately makes its raison d'être futile. A method of comparative law will be used to evaluate other models of enforcement and regulation by internationally recognised corporate governance codes and legislation in the United Kingdom, United States of America, South Africa and The Organisation for Economic Co-operation and Development (OECD). The objective is to try to answer the questions of what measures work well and to what extent; this information is used to ascertain which model would be suitable for Zambia to address the problems of regulation and enforcement. It should be noted however from the outset that this paper does not advocate for a 'copy and paste' modus operandi in responding to the challenges of corporate governance in Zambia. There is no one formula to answer economic corporate governance issues but these policies which have been successful elsewhere can be used as a basis to create an organic formulae that would ultimately be suitable for Zambia, taking into account the issues that are unique to its business culture, fiscal policies and economic growth among others.